The Relation between Knowledge and Belief with Adult Patient’s Antibiotics Use Adherence - April Nuraini; Rika Yulia; Fauna Herawati; Setiasih Setiasih (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The inappropriate use of antibiotics has resulted in bacterial resistance to antibiotics. One of the factors supporting this phenomenon is the lack of patient knowledge and belief of antibiotics. The study aimed to know the relationship between knowledge and belief with adherence in using antibiotics in adult patients at Syarifah Ambami Rato Ebu Hospital, Bangkalan, based on the Health Belief Model theory. This research is observational analysis using cross-sectional study. There were 103 patients chosen by incidental sampling. Data collection about knowledge was obtained through questionnaires containing 13 questions, while one about belief used a questionnaire containing 30 valid and reliable questions. Adherence was measured by the pill count method. The relationship between knowledge and belief to adherence was analyzed using logistic regression test. The relationship between demography and adherence was analyzed using Spearman correlation test with α = 0.05. The result of this research shows that most patients had sufficient knowledge (57,2%), sufficient belief (69,9%) and adherence (55,3%). There was a significant relationship between knowledge with adherence in the use of antibiotics (p = 0.011) and a significant relationship between belief and adherence in the use of antibiotics (p = 0.046). In terms of belief, perceived benefits have a significant effect on adherence. The conclusions of this study is that there is a relationship between knowledge and belief with adherence in the use of antibiotics and in accordance with health belief model (HBM) theory.